Penilaian Terjemahan Lagu Doraemon No Uta Sebagai Opening Animasi Doraemon - Nela Naila Nidhafar; Yenny Aristia Nasution; Arza Aibonotika (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
This research is a qualitative research method regarding the assessment of Doraemon no Uta as an opening song of Doraemon animation. The purpose of the study is to explain how to objectively assess the translation of Doraemon no Uta song from Doraemon animation and find out how well the translations of the song is based on Newmark's assessment. According to Newmark, the assessment of translation is divided into four criterias, including: 1) translation as a science; 2) translation as a craft; 3) translation as art; and translation as taste. The lyrics of the song Doraemon no Uta in the source language (SL) and target language (TL) are collected in a table, then the score is determined for each criterion. The scores are sum up and the total is divided by the number of lyrics which is assessed. It was found that the translation category for the song Doraemon no Uta’s translation’s score is 79.28, which went to the translation category A (very good).